The Impact of Adolescent Motherhood on Education in Chile - Matias Berthelon; Diana Kruger (Institute for the Study of Labor (IZA), 2014)
We analyze the effect of having a child in adolescence on high school completion, educational attainment, and college enrollment in a developing country setting using nine repeated rounds of Chilean household surveys that span the 1990–2009 period. We control for selection bias and household unobservables of teen motherhood with two approaches: different estimation methods – propensity score matching and family fixed effects for a large sub-sample of sisters – and three different samples. Results reveal that adolescent motherhood reduces the probability of high school completion by between 18 to 37 percent. Furthermore, effects are heterogeneous across education groups: teen motherhood has larger negative effects on high school completion and years of schooling among poor and low-education households. Our results imply that policies aimed at reducing early childbearing will have important short-term effects on young women's education outcomes.
Keywords: O15; J13; I25; 330; education; teen pregnancy; adolescent motherhood; youth; high school; Chile